Determinants of Unemployment in 5 ASEAN Countries with Population as Moderation - Rafli Hidayatullah, M; Hidayat Riyanto, Wahyu (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
Total workforce unemployment occurred in ASEAN's 5 countries, namely Indonesia, Singapore, Thailand, the Philippines, and Malaysia, from 2001 to 2021, with the population variable as a moderating variable. The regression analysis in this study uses two models. Using two regression models is intended to compare the test results of the two regression models. The first regression model tests the effect of the two independent variables on the dependent variable. At the same time,​ the second regression model tests the impact of the moderating variables. The results of Partial Testing in this study indicate that Investment significantly negatively impacts unemployment. GDP growth has a positive and insignificant effect on unemployment, and inflation has a considerable positive impact on unemployment. Meanwhile, the Results of the Moderated Regression Analysis Test in this study show that the population is unable to moderate (weaken) the effect of Investment and GDP Growth on unemployment. Besides that, this study shows that the population can moderate (strengthen) the impact of inflation on unemployment.